Gender disparities in specialized nephrology care - Frida Welander; Barbara Salzinger; Stefan H Jacobson; Juan-Jesus Carerro; Marie Evans (Clinical Kidney Journal, 2026)
Abstract Background Although women have more prevalent chronic kidney disease (CKD) they less often have recommended therapy or a documented CKD diagnosis in primary care. This study investigates whether gender disparities remain in specialized nephrology care as a possible expression of gender bias. Methods Patients with incident eGFR <30ml/min/1.73m2 registered in the Swedish Renal Registry (SRR-CKD) between 2010-2020 were included. Logistic regression investigated gender differences in having a CKD diagnosis, kidney biopsy, blood pressure <140/90mmHg (BP) and guideline-recommended medications. Gender disparities regarding kidney replacement therapy (KRT) initiation including preemptive kidney transplantation and initiating dialysis with a planned access were investigated using flexible parametric regression and Cox regression. Results Of 25478 included patients 37% were female. Women were less likely to have a CKD diagnosis, odds ratio (OR) 0.81 (95% confidence interval 0.73-0.90), a RAASi (OR 0.94, 0.89-0.99), lipid-lowering agent (OR 0.93, 0.88-0.99) and BP <140/90mmHg (OR 0.91, 0.86-0.97). Women had borderline-significantly lower odds of having a kidney biopsy 0.93 (0.86-1.00). Women were less likely to initiate KRT, hazard ratio (HR) 0.75 (0.70-0.80) and initiate dialysis with a planned access (HR 0.82, 0.78-0.85). No significant gender differences were seen regarding preemptive transplantation and conservative kidney management (CKM) decision. Women died less often before KRT initiation (HR 0.81, 0.77-0.85). Conclusions Swedish women with advanced CKD in specialized nephrology remain underdiagnosed, undertreated and less likely to reach blood pressure targets. Although these gender differences didn’t translate to increased KRT and mortality rates, they highlight the need for nephrologists to maintain awareness and strive for health equity.